Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)